2008
DOI: 10.1016/j.jcf.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Zinc therapy for night blindness in cystic fibrosis

Abstract: This is the first report of a supplemented CF patient presenting with clinical vitamin A deficiency to be successfully treated with zinc therapy alone. Therefore in addition to retinol supplementation, normalizing serum zinc levels may be important in maintaining the vitamin A status of CF patients. The interactions and synergistic effects between the two micronutrients are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…15 An increase has been observed in the sputum zinc levels in pulmonary exacerbations, and a decrease has been observed in the levels after treatment in bronchiectasis (cystic fibrosis and non-cystic fibrosis bron- chiectasis); however, the significance of this remains unclear. 16 Tinley et al 17 observed an interaction between the serum zinc and vitamin levels. They reported an improvement in the zinc levels after supplementation with retinol.…”
Section: Discussionmentioning
confidence: 98%
“…15 An increase has been observed in the sputum zinc levels in pulmonary exacerbations, and a decrease has been observed in the levels after treatment in bronchiectasis (cystic fibrosis and non-cystic fibrosis bron- chiectasis); however, the significance of this remains unclear. 16 Tinley et al 17 observed an interaction between the serum zinc and vitamin levels. They reported an improvement in the zinc levels after supplementation with retinol.…”
Section: Discussionmentioning
confidence: 98%
“…Previous case studies have highlighted the importance of zinc in the treatment of night blindness, with one case study using zinc alone to successfully treat it. 10 , 13 This boy's zinc was within the normal range; however, only 0.1% of zinc is located in the serum, so it is a poor indicator of zinc status 14 . Zinc deficiency could have been a cause, but by giving the 6 ADEK tablets per day, we were giving 45 mg of zinc per day and thus treating any zinc deficiency that may have been present…”
Section: Discussionmentioning
confidence: 99%
“…17 Zinc supplementation alone led to resolution of nyctalopia in a patient with cystic fibrosis with combined zinc and vitamin A deficiency. 18 ERG rod responses improved dramatically after zinc supplementation. ERG characteristics of zinc deficiency include diminished scotopic A-and B-wave amplitudes; B-wave amplitudes may be affected to a greater degree.…”
Section: Zinc Deficiency and Retinal Physiologic Manifestationsmentioning
confidence: 91%